Reaching Out to the Child : An Integrated Approach to Child Development - World Bank (Washington, DC, 2013)
While India has, over the last few decades, made considerable progress in ensuring child survival and basic education, much remains to be done. When the major indicators for the Indian child's development -- maternal mortality, birth weight, immunization, nutrition level and basic education - are compared with those of other developing countries, it is clear that the Indian child urgently needs better interventions. In the context of such a situation, the vision for the future has to be an India where all children have all the chances they need for optimal development. The emerging question is, despite significant investments and a conducive policy framework, why is the status of the Indian child still far from satisfactory? And, what then is the way forward to realize this vision? It was in this context that a multi-sectoral workshop entitled "Reaching Out to the Child" was organized collaboratively by the Education and Health, Nutrition and Population teams of the World Bank on February 21 and 22, 2000 with the participation of Indian professionals from health, nutrition and education sectors; and senior representatives of the Departments of Health, Education, and Women and Child Development (WCD). The objective of the workshop was to initiate multi-sectoral discussions across the government and non-government sectors with the aim of establishing a constituency for the development of an integrated, comprehensive and convergent approach to child development. This report synthesizes the observations and conclusions from the five studies and the deliberations of the seminar, supplemented by review of other relevant documentation. The starting point of this report's conceptual framework is the premise that the child's development must be viewed along the prenatal to11+ age continuum as a continuous and cumulative process. Investment and intervention have to take into account every sub-stage of the child's development process, from conception through the years of growth to enable the child at 11+ years to reach the basic milestone of successful completion of primary school. Moreover, intervention must account for the dynamic, interactive relationship among the sub-stages of development; among sectors such as health, nutrition and education; and among aspects such as maternal health, psychosocial development, and family and community environments. The continuous and cumulative nature of impact has also meant that the impact of not attaining appropriate developmental milestones, or health and nutritional outcomes, or learning capacities, will accompany the child to the next stage. In some cases, "cumulative" failure is the result of an inter-generational transfer of handicaps, and the accompanying downward spiral of poverty, ill health, malnutrition, and poor learning outcomes for children. For the purposes of the quantitative and qualitative data studies conducted for this report, the framework underlined the critical and reciprocal link between health and education, specifically in relation to children, whereby poor health and nutrition work as barriers to attendance and educational attainment/achievement. The family, the community, the state, service delivery mechanisms, and the presence of non-governmental organizations, all play important mediating roles and further fragment the experience at the grassroots.